СПОРТ ФАОЛИЯТИДА НАТИЖАГА ЭРИШИШ ПСИХОЛОГИК МУАММО СИФАТИДА - Усмонов, Э.М. (SCIENCE and SOCIETY, 2023)
This article is devoted to the topic of achieving results in sports as a psychological problem. The article also discusses the psychological characteristics of sports, sports motives and their manifestation, success motives, psychological aspects of competitiveness, pride in sports, self-satisfaction, goal-orientation, intensity of sports, pride in sports, the need for success, are also covered in detail issues such as internal and external control mechanism in sports, special skills in sports.